The Role of Knowledge and Innovation Management in MSMEs’ Performance: The Moderating Effect of Firm Size - Hardi Hardi; Afred Suci; Abu Amar Fauzi (STI Policy and Management Journal, 2025)
While the effect of knowledge management (KM) in predicting firm innovation and performance has been extensively documented in large enterprises, its dynamics within micro, small, and medium-sized enterprises (MSMEs) are relatively underexplored. The current study surveyed 174 Indonesian MSMEs, employed Hayes PROCESS Macro to investigate the KM-innovation-performance pathways with firm size as a moderator. The findings reveal that medium-sized firms exhibited the greatest KM practices, innovation, and performance. KM significantly enhanced innovation and performance, while innovation had no significant impact. Firm size strengthened the KM-innovation-performance linkage, while the KM-innovation-performance mediation and its size conditional effects were positive yet marginally insignificant. Theoretical and practical contributions are also discussed, and recommendations for further studies are also proposed.